The radical right in Britain : social imperialism to the BNP - Sykes, Alan, 1942- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2005)
In many and varied forms, the Radical Right has been a hyper-nationalist thorn in the side of Britain's liberal political system for over 100 years. This survey examines its troublesome history, and its critique of British society, from its origins in Edwardian fears of imperial disintegration and racial decay to the current resurgence of the newly modernized British National Party.
Introduction: Some Pointers Towards a Definition -- Social Imperialism and Racial Regeneration -- Patriotic Labour and International Conspiracies -- Sir Oswald Mosley and British Fascism -- Alternative Economics and Peace-Loving Patriots -- The Union Movement and the National Front -- Warrior Saints and Men in Suits -- Conclusion: Past Failures and Future Prospects.
Includes bibliographical references (p. 152-175) and index.
Further reading: p. [176]-179.
The Roger Griffin ComFas Collection
Keywords: British National Party (1982- ); Radicalism -- Great Britain -- History -- 20th century; Fascism -- Great Britain -- History -- 20th century